Association between gratitude, the brain and cognitive function in older adults: Results from the NEIGE study. (May 2022) - Tani, Yukako; Koyama, Yuna; Doi, Satomi; Sugihara, Genichi; Machida, Masaki; Amagasa, Shiho; Murayama, Hiroshi; Inoue, Shigeru; Fujiwara, Takeo; Shobugawa, Yugo
Highlights: Gratitude were associated with better cognitive function among older adults. Gratitude were associated with larger volumes of amygdala and fusiform gyrus. Amygdala mediated the association between gratitude and a cognitive function. Abstract: Objectives: Having gratitude is associated with reduced social isolation and depression, which are risk factors for dementia. However, it is unknown whether gratitude is directly associated with cognitive function. This study aimed to determine associations between gratitude and cognitive function and to elucidate the underlying biological mechanism by testing the mediating role of brain regions among healthy older people. Methods: We used cross-sectional data from the 2017 Neuron to Environmental Impact across Generations (NEIGE) study of community-dwelling older adults aged ≥ 65 years ( n = 478). Cognitive function was assessed using the Mini-Mental State Examination (MMSE). Levels of gratitude were assessed using the two-items of Gratitude Questionnaire. Volumes of brain regions associated with emotional processing and social interaction were measured by magnetic resonance imaging. Linear regression models and structural equation models were used to examine associations between level of gratitude, brain volume, and cognitive function. Results: The mean gratitude score was 6.3 (SD=0.9) and the mean MMSE score was 27.1 (SD=2.5). Regression analysis showed that higher levels of gratitude were associated with better cognitive function (coefficient=0.25, 95% CI: 0.01, 0.49), adjusting for age, sex, education, marital status, and depressive symptoms. Higher levels of gratitude were associated with larger volumes of right amygdala and left fusiform gyrus. Structural equation model analysis showed that amygdala volumes mediated the association between gratitude and cognitive function. Conclusion: Higher levels of gratitude were positively associated with cognitive function, partially mediated through the amygdala, which is involved in processing emotion and memory.